SARS-CoV-2 neutralizing antibody responses are more robust in patients with severe disease - Pengfei Wang; Lihong Liu; Manoj S. Nair; Michael T. Yin; Yang Luo; Qian Wang; Ting Yuan; Kanako Mori; Axel Guzman Solis; Masahiro Yamashita; Ankur Garg; Lawrence J. Purpura; et al. (Emerging Microbes and Infections, 2020)
ABSTRACTWe studied plasma antibody responses of 35 patients about 1 month after SARS-CoV-2 infection. Titers of antibodies binding to the viral nucleocapsid and spike proteins were significantly higher in patients with severe disease. Likewise, mean antibody neutralization titers against SARS-CoV-2 pseudovirus and live virus were higher in the sicker patients, by ∼5-fold and ∼7-fold, respectively. These findings have important implications for those pursuing plasma therapy, isolation of neutralizing monoclonal antibodies, and determinants of immunity.